Establishment of An Academic Makerspace at the Bataan Peninsula State University: Prospects and Challenges - Macaraeg, Emmanuel Calvento; Rivera, Cristina Gutierrez; Dela Rosa, Ronnell Dominguez; Dizon, John Ryan Cortez (Advance Sustainable Science, Engineering and Technology, 2021)
Makerspaces are now fixtures in smart cities and universities in advanced countries. Many universities, especially in the United States, have Academic Makerspaces serving students and faculty, helping them with their projects. In Bataan Peninsula State University our goal is to have an Academic Makerspace with services and facilities at par with international standards. This Academic Makerspace will be a place where our students can ideate, conceptualize, build and manufacture their projects, either academic projects,Â  or just extracurricular projects they are interested in. The goal is to promote invention, innovation, creation and making. This study summarized the best practices of Academic Makerspaces in the United States. The practices of local innovation centers were also benchmarked. With this study, we have identified what facilities are needed, which equipment to purchase, and what kinds of programs should be made available in the Makerspace. Fund source, possible partner agencies, and other important details have been discussed. This study provides short- and long-term plans/programs which would be very important in the establishment of BPSUâ€™s Academic Makerspace. These plans will be used to recommend future facilities/services in BPSU. The prospects and challenges of establishing an academic makerspace which would need careful consideration have been briefly discussed.